Modal Sosial Pengobatan Alternatif Pada Masyarakat Desa Penuba Kabupaten Lingga - Sudarti, Sartika; Wahyuni, Sri; Syafitri, Rahma (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2023)
The phenomenon of alternative medicine in Lingga Regency, there is treatment directly or from telephone media which is an option for people to get treatment. The purpose of this study is to find out how is social capital in alternative medicine in the community in Penuba village in Lingga Regency. The theory used in this study is the theory of social capital from Robert D. Putnam. The methtod the research used in this study is a qualitative method. Data collection techniques in this study are observation, intervies and documentation. Informants in this study amounted to 10 people selected by purposive sampling. The data analysis technique used is data reduction, data presentation, and drawing conclusions/verification. The findings in this study are that alternativemedicine from mobile media has existed since 2008 until now, the existence of traditional healers is very strong due to strong social capital. Which consists of beliefs, norms, and also the network that is formed in society. Communities that are far away also have a connection with the dukun due to social capital. Trust because they know each other and know the knowledge and abilities possessed by traditional healers in treating a disease, and there are values of togetherness among patients, family, relatives and friends in obtaining alternative medicine, and there is a network between traditional healers, patients, families, relatives and friends who inform each other about alternative medicine. Cooperate with each other in getting treatment in order to achieve the goal of healing.